Denied Suicide Attempt: Penetrating Cranial Cerebral Injury with a Nail Gun - Lang, Josef Michael; Krauss, Joachim K. (Indian Journal of Neurotrauma, 2017)
Penetrating craniocerebral injuries with a nail gun are uncommon. In this article, we describe a highly unusual delayed presentation of a 49-year-old man after an initially unnoticed penetrating head injury with an air-powered nail gun. The nail was successfully surgically removed, and the postoperative course was uneventful. Further evaluation revealed that the penetrating craniocerebral nail gun injury was a suicide attempt and not an accident. Possible reasons for the initial unrecognition of the injury and denial of the suicide attempt were discussed.
Keywords: nail gun; head trauma; penetrating head injury